Development of Animated Videos in Pancasila and Citizenship Education Lessons to Improve Students' Courtesy Attitude in Primary School 050753 Perlis - Tarigan, Salamah; Adella, Sherly; Ramadhani, Renni (International Journal of Students Education, 2024)
Pancasila and citizenship education is learning to apply moral and religious values to students through science and these values are applied to oneself, family, friends, educators, and the people around them, or to God. The social growth of elementary school children has been carried out from an early age, such as being polite and respecting parents. However, there are still many elementary school students who still do not apply these polite attitudes. Therefore, we conducted research on students at SD 050753 Perlis using animated videos as a learning medium for PPKN. The aim of this research is to improve the polite attitudes of SD 050753 students by developing animated videos in Pancasila and citizenship education lessons. The method used in this research is Research and Development (R&D) with 5 stages, namely Analyze, Design, Development, Implementation, Evaluate. The results of this research were that 97% of the students felt interested in the new learning system using animated video media and the results of the interview tests conducted with the students also showed that the students' level of politeness had increased. The research conclusions obtained from the development of this animated video show the effectiveness of improving students' polite attitudes and increasing students' interest in learning Pancasila and citizenship education.